HLA‐matched related peripheral blood stem cell and bone marrow transplantation with RIC regimens yield comparable outcomes for adult AML - Takaya Mitsuyoshi; Yasuyuki Arai; Tadakazu Kondo; Takahito Kawata; Shigeki Hirabayashi; Masatsugu Tanaka; Yasuo Mori; Noriko Doki; Tetsuya Nishida; Takeharu Kotani; Masao Ogata; Takayuki Tabayashi; et al. (eJHaem)
Abstract Introduction Understanding differences in clinical outcomes between PBSCT and BMT is important, and this study compared outcomes of HLA‐matched related PBSCT and BMT using reduced‐intensity conditioning (RIC) in adult acute myeloid leukemia (AML) patients. Methods Data from 402 patients who underwent either PBSCT (n = 294) or BMT (n = 108) between 2000 and 2022 were analyzed using the Japanese nationwide registry database. The primary endpoint was overall survival (OS), and secondary endpoints included disease‐free survival (DFS), non‐relapse mortality (NRM), and GVHD. Results Results indicated no significant difference in 3‐year OS (44.6% for PBSCT vs. 46.9% for BMT, HR 1.173, P = 0.299) and DFS (42.1% vs. 41.8%, HR 1.073, P = 0.639). PBSCT was more beneficial for avoiding relapse (20.3% vs. 12.4%, HR, 0.715, P = 0.059). However, PBSCT was associated with higher NRM (20.3% vs. 12.4%, HR 1.801, P = 0.025) due to more frequent, chronic GVHD (HR 1.889, P = 0.035). Subgroup analysis did not reveal specific patient groups that benefited more from PBSCT or BMT. Incidence of extensive chronic GVHD and NRM has improved in PBSCT recipients in recent years (2014–2022). Conclusions We conclude that related PBSCT with RIC regimens offers comparable prognosis to BMT for adult AML patients. Further optimization of prophylactic strategies for chronic GVHD is required to improve outcomes after PBSCT.